Ethnic differences in success at application for consultant posts among United Kingdom physicians from 2011 to 2019: a retrospective cross-sectional observational study. (August 2022) - Harvey, PR; Phillips, C; Newbery, N; Nagamoottoo, D; Woolf, K; Trudgill, NJ
Summary: Objectives: To identify associations between success following application for consultant physician posts and demographic factors. Design: Logistic regression analysis of nationwide survey data. Setting: United Kingdom (UK) physicians with a recent certificate of completion of training (CCT). Participants: All UK trainee physicians who received a CCT between 2010 and 2019 were surveyed. Respondents were excluded if they had not applied for a consultant post or if application data were incomplete. Main outcome measures: The primary outcome measure was success over the entire consultant application process, i.e. shortlisted and offered the post following the first application. Secondary outcomes were: shortlisted following first application and offered a consultant post at first interview. Results: From 7037 CCT holders surveyed, 50.7% responded. While 1198 (59.7%) respondents were white, 760 (37.9%) were from minority ethnic groups and 50 (3.5%) were of unknown ethnicity. Primary medical qualification (PMQ) country was the UK in 75.3% (n = 1512). On multivariable logistic regression analysis the independent negative associations with success were: minority ethnicity (odds ratio [OR] 0.55, 95% confidence interval [CI] 0.43–0.71); p < 0.001) vs. white; PMQ from Europe (OR 0.47, 95% CI 0.28–0.79; p = 0.004) or Asia (OR 0.68, 95% CI 0.49–0.96; p = 0.027) vs. UK PMQ; year of CCT 2012 (OR 0.40, 95% CI 0.24–0.68; p = 0.001), 2013 (OR 0.39, 95% CI 0.23–0.65; p < 0.001), and 2014 (OR 0.26, 95% CI 0.15–0.43; p < 0.001) vs. 2019. Specialties associated with lower success rates included Cardiology, Endocrinology, Genitourinary medicine, Palliative care, Renal and Respiratory, compared to Acute medicine. Conclusions: Minority ethnic group candidates for consultant physician posts had lower success rates compared to white candidates after correction for important variables including specialty, time from and country of PMQ. This finding requires further evaluation to identify the causes for this variation.